Optimizing the brand awareness of Gaia Daily and Zuist Leather MSME through the Go online system - Harto, Budi; Wahyuni, Ning; Sumarni, Teti (Universitas Ahmad Dahlan, Yogyakarta, 2021)
In the current era, where information is absorbed and moved as fast as it is today, every effort needs to keep up with technology development. This program can help existing efforts to help build brand awareness in the public's eyes, find new markets or customers, and increase sales. GAIA Daily and Zuist Leather, as one of the MSMEs in Bandung Indonesia, need this program to increase brand awareness and find new markets. This optimization activity by (1) Providing training on the Internet and its benefits for marketing purposes by doing marketing planning; (2) Provide social media management training such as Instagram and Facebook; (3) Provide training on advertising on social media through Instagram Ads and Facebook Ads. GAIA Daily and Zuist Leather Genuine Leather have been proven by the Go Online System that has been done through Social Media. The results are very good, where Gaia Daily and Zuist Leather Genuine Leather social media has gained market reach and new potential consumers as many as 1,157,119 people from the online platforms used today. This can help MSMEs GAIA Daily and Zuist Leather Genuine Leather increase sales turnover while raising brand awareness in the eyes of its regular consumers.